2017
DOI: 10.1038/s41598-017-16353-x
|View full text |Cite
|
Sign up to set email alerts
|

The microbiomes of blowflies and houseflies as bacterial transmission reservoirs

Abstract: Blowflies and houseflies are mechanical vectors inhabiting synanthropic environments around the world. They feed and breed in fecal and decaying organic matter, but the microbiome they harbour and transport is largely uncharacterized. We sampled 116 individual houseflies and blowflies from varying habitats on three continents and subjected them to high-coverage, whole-genome shotgun sequencing. This allowed for genomic and metagenomic analyses of the host-associated microbiome at the species level. Both fly ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 72 publications
2
65
0
5
Order By: Relevance
“…An interesting hypothesis of H. pylori transmission was suggested by Junqueira et al in Brazil. The authors hypothesized that insects, in particular blowflies and houseflies, might be responsible for the transmission as they feed with and breed in fecal material.…”
Section: Factors Associated With Helicobacter Pylori Infectionmentioning
confidence: 95%
“…An interesting hypothesis of H. pylori transmission was suggested by Junqueira et al in Brazil. The authors hypothesized that insects, in particular blowflies and houseflies, might be responsible for the transmission as they feed with and breed in fecal material.…”
Section: Factors Associated With Helicobacter Pylori Infectionmentioning
confidence: 95%
“…In Peru, H pylori DNA was identified in drink water samples . Likewise, in Brazil, Junqueira et al hypothesized that domestic insects, such as flies, may be related to the transmission of H pylori , due to their feeding and reproduction in fecal material . Intrafamilial transmission is considered the main means of H pylori acquisition during early childhood .…”
Section: Introductionmentioning
confidence: 99%
“…12 Likewise, in Brazil, Junqueira et al hypothesized that domestic insects, such as flies, may be related to the transmission of H pylori, due to their feeding and reproduction in fecal material. 13 Intrafamilial transmission is considered the main means of H pylori acquisition during early childhood. 11,14 Crowding, 8,15 the presence of H pylori infection in mothers, 16,17 the presence of older siblings, [15][16][17][18] and lower socioeconomic status 8,19,20 are suggested as the major risk factors for H pylori infection.…”
mentioning
confidence: 99%
“…Studies have shown that microbes can be attached to the legs (Kobayashi et al, 1999), wings (Ordax et al, 2015;Tan et al, 1997;Yap et al, 2008), or other body parts, including the mouthparts (Geden et al, 2008;Sela et al, 2005). The report by Junqueira et al (2017) examined 116 individual blowflies and houseflies on three continents using high-coverage, whole-genome shotgun sequencing and reported that the legs/wings showed the greatest microbial diversity; and, the authors suggested these two fly structures provided an important microbial dispersal route. What needs to be done is to evaluate how long microbes can remain on the legs and wings because of the immense amount of fly grooming.…”
Section: Mouthpartsmentioning
confidence: 99%
“…Historically, and even recently, most pathogen research concerning adult dipterans has focused on the midgut (Lehane and Billingsley, 1996) and hindgut (Christofi and Apidianakis, 2013), ignoring the foregut. At the same time, some authors ( Junqueira et al, 2017;Tomberlin et al, 2017) present reviews and papers on the association between flies and their bacterial interactions, but focus mainly on identifying the microbes found in the guts of field collected flies with no reference as to where the microbes might be within the guts (i.e. foregut, midgut, or hindgut).…”
Section: General Introductionmentioning
confidence: 99%